Effects of occupational dust exposure on the health status of workers in China - Minhua Li; Chuancheng Wu; Yilin Zhang; Yu Jiang; Jinfeng Lin; Jianjun Xiang (Scientific Reports)
Abstract This cross-sectional study examined the health impacts of occupational dust exposure on workers in Fujian Province, China, using data collected from 2020 to 2021. The primary objective was to assess the associations between occupational dust exposure and several adverse health outcomes, including abnormal chest X-ray (Abn-CXR), abnormal pulmonary function tests (Abn-PFTs), pneumoconiosis (PC), abnormal electrocardiograms (Abn-ECGs), abnormal liver function tests (Abn-LFTs), hypertension (HTN), and hearing loss (HL). logistic regression models were employed to identify significant risk factors. Stratified analyses by age and gender were performed to evaluate demographic differences in health risks. The results showed that workers currently employed, those with over 10 years of dust exposure, and workers exposed to silica, cement, or coal dust had a higher risk of Abn-CXR, Abn-PFTs, PC, Abn-ECGs, Abn-LFTs, HTN, and HL. Stratified analyses further revealed that male workers and individuals over 40 years old experienced a higher risk of abnormal health outcomes. These findings underscore the urgent need for targeted interventions, improved protective measures, and stricter occupational safety regulations to reduce the health burden associated with dust exposure in the workplace.